The mountainous Cretan dietary patterns and their relationship with cardiovascular risk factors: the Hellenic Isolated Cohorts MANOLIS study. Issue 6 (19th December 2016) - Farmaki, Aliki-Eleni; Rayner, Nigel William; Matchan, Angela; Spiliopoulou, Panagiota; Gilly, Arthur; Kariakli, Vasiliki; Kiagiadaki, Chrysoula; Tsafantakis, Emmanouil; Zeggini, Eleftheria; Dedoussis, George
Abstract: Objective: We carried out de novo recruitment of a population-based cohort (MANOLIS study) and describe the specific population, which displays interesting characteristics in terms of diet and health in old age, through deep phenotyping. Design: Cross-sectional study where anthropometric, biochemical and clinical measurements were taken in addition to interview-based completion of an extensive questionnaire on health and lifestyle parameters. Dietary patterns were derived through principal component analysis based on a validated FFQ. Setting: Geographically isolated Mylopotamos villages on Mount Idi, Crete, Greece. Subjects: Adults ( n 1553). Results: Mean age of the participants was 61·6 years and 55·8 % were women. Of the population, 82·7 % were overweight or obese with a significantly different prevalence between overweight men and women (43·4 v . 34·7 %, P =0·002). The majority (70·6 %) of participants were married, while a larger proportion of women were widowed than men (27·8 v . 3·5 %, P <0·001). Smoking was more prevalent in men (38·7 v . 8·2 %, P <0·001), as 88·8% of women had never smoked. Four dietary patterns emerged as characteristic of the population; these were termed 'local', 'high fat and sugar, 'Greek café/tavern' and 'olive oil, fruits and vegetables'. Individuals more adherent to the local dietary pattern presented higher blood glucose ( β =4·026, P <0·001). Similarly, individuals with higher compliance with the Greek café/tavern pattern had higher waist-to-hip ratio ( β =0·012, P <0·001), blood pressure ( β =1·015, P =0·005) and cholesterol ( β =5·398, P <0·001). Conclusions: Profiling of the MANOLIS elderly population identifies unique unhealthy dietary patterns that are associated with cardiometabolic indices.